The visual-verbal text interrelation: Lessons from the ideational meanings of a phonics material in a primary level EFL textbook - Ahmad Sugianto; Devi Andriyani; Ilham Agung Prasetyo (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
The interrelation between verbal and image represented in a textbook is one of the prominent issues that should be taken into account. If the interrelation between these modes is presented in a textbook properly and aptly, students' outcomes of a particular material, such as phonics, may be entrenched and fostered. Thereby, this study aimed to scrutinize the interrelation between the verbal and image represented in the phonics material, which was to the best of the writer's knowledge concerning studies scrutinizing the phonics materials vis-à-vis multimodal text was still limited. Furthermore, a qualitative research method using content analysis was employed to investigate the analysis unit, namely the phonics material taken from one primary level EFL textbook. Besides, Royce's (1998, 2002, 2007) Intersemiotic Complementarity and Kress and van Leeuwen's (2006) Grammar of Visual Design involving one of the metafunctions deriving from Halliday's Systemic Functional Linguistics, ideational metafunction was employed. The findings revealed that a multimodal text encompassing the phonic material was, in fact, had fruitful meanings manifested in various modes, and there was a synergy found between the visual and verbal meanings realized by the ideational intersemiotic complementarity.